2015
DOI: 10.1111/pere.12108
|View full text |Cite
|
Sign up to set email alerts
|

Agents' self‐esteem moderates the effectiveness of negative‐direct partner regulation strategies

Abstract: Prior research suggests that trying to change partner's attitudes and behaviors in hostile and demanding ways can successfully produce desired changes in targeted partners. The current research investigated whether the effectiveness of negative-direct partner regulation strategies depends on the self-esteem of regulation agents. Two longitudinal studies, involving individuals (N = 156) and couples (N = 174) in ongoing relationships, assessed agents' partner regulation attempts, the regulation strategies agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Of importance, these results are both consistent with and advance the wider communication literature. They are consistent with emerging evidence that dispositions of agents and targets can modify the impact of communication strategies (Baker & McNulty, ; Jayamaha & Overall, ), but are the first to illustrate the factors of targeted partners that moderate receptivity to negative‐indirect partner regulation strategies in particular. Moreover, the specific ways in which attachment insecurity is associated with the use and effectiveness of negative‐indirect regulation strategies demonstrates that the factors that modify the impact of specific strategies are those that are relevant to the particular ingredients and working mechanisms of those strategies.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Of importance, these results are both consistent with and advance the wider communication literature. They are consistent with emerging evidence that dispositions of agents and targets can modify the impact of communication strategies (Baker & McNulty, ; Jayamaha & Overall, ), but are the first to illustrate the factors of targeted partners that moderate receptivity to negative‐indirect partner regulation strategies in particular. Moreover, the specific ways in which attachment insecurity is associated with the use and effectiveness of negative‐indirect regulation strategies demonstrates that the factors that modify the impact of specific strategies are those that are relevant to the particular ingredients and working mechanisms of those strategies.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, consistent with the effects reported here, resistance to change by targets undermines immediate conflict resolution and predicts less improvement over time (Overall, Sibley, & Tan, ; Overall et al, , ). Lower regulation success is also consistently associated with growing dissatisfaction and negative relationship evaluations (Hira & Overall, ; Jayamaha & Overall, ; Overall et al, , ). Thus, because the negative‐indirect regulation strategies utilized by highly anxious individuals do not generate desired change, and negative‐indirect regulation strategies are particularly ineffective in motivating change by highly avoidant targets, they will play an important role in producing poor downstream outcomes for relationships involving insecure partners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the current focus on affective associations, targets may be more likely to attribute affect resulting from actors' typical partner-regulation behaviors to those actors and more likely to attribute it to something else (e.g., the problem, self) when it is atypical of those actors, and such emerging associations should have important implications for motivation. Research is consistent with these ideas (e.g., Forest, Kille, Wood, & Holmes, 2014;Jayamaha & Overall, 2015). In one study, Jayamaha and Overall (2015) demonstrated that oppositional behaviors motivated less change in targets when enacted by actors with low self-esteem, who tend to overact to problems (e.g., Lemay & Dudley, 2011), than when enacted by actors with high self-esteem.…”
Section: How Partner-regulation Behaviors Shape Evaluationsmentioning
confidence: 81%
“…Research is consistent with these ideas (e.g., Forest, Kille, Wood, & Holmes, 2014;Jayamaha & Overall, 2015). In one study, Jayamaha and Overall (2015) demonstrated that oppositional behaviors motivated less change in targets when enacted by actors with low self-esteem, who tend to overact to problems (e.g., Lemay & Dudley, 2011), than when enacted by actors with high self-esteem. Similarly, Forest and colleagues (2014) demonstrated that targets are more responsive to the demands of actors who are infrequently negative compared to actors who are chronically negative.…”
Section: How Partner-regulation Behaviors Shape Evaluationsmentioning
confidence: 81%